Impact of dose-dense neoadjuvant chemotherapy on pathologic response and survival for HER2-positive breast cancer patients who receive trastuzumab - Lize Wang (Nature Portfolio, 2021)
Abstract To compare outcomes in patients with human epidermal growth factor receptor-2 (HER2)-positive breast cancer who received either dose-dense neoadjuvant chemotherapy (NAC) with trastuzumab or standard-interval chemotherapy with trastuzumab. Patients with HER2-positive breast cancer who received NAC, including epirubicin and cyclophosphamide followed by paclitaxel with trastuzumab were included. Patients were divided into either the dose-dense or standard-interval group. We compared pathologic complete remission (pCR), distant disease-free survival (DDFS), event-free survival (EFS), and breast cancer-specific survival (BCSS) between the two groups. Two hundred (49.6%) patients received dose-dense NAC, and 203 (50.4%) received standard-interval NAC. The pCR rate was 38.4% in the dose-dense group and 29.2% in the standard-interval group (P = 0.052). In patients with lymph node (LN) metastases, the LN pCR rate was 70.9% in the dose-dense group and 56.5% in the standard-interval group (P = 0.037). After a median follow-up of 54.6 months, dose-dense chemotherapy presented an improvement on DDFS (hazard ratio [HR] = 0.49, 95% confidence interval [CI]: 0.19–1.28, EFS (HR = 0.54, 95% CI: 0.24–1.21), and BCSS (HR = 0.41, 95% CI: 0.11–1.51), but the difference was not significant. Compared with standard-interval chemotherapy, dose-dense chemotherapy resulted in a superior 5-year DDFS (100% vs. 75.3%, P = 0.017) and 5-year EFS (96.9% vs. 78.3%, P = 0.022) in patients younger than 40 years. HER2-positive patients can achieve a higher LN pCR rate with dose-dense NAC than with standard-interval NAC with trastuzumab. Better survival may also be achieved with dose-dense chemotherapy with trastuzumab than with standard-interval chemotherapy with trastuzumab among young patients (age ≤ 40 years).